TINGKAT KEBERSIHAN LANTAI RUANG PERSALINAN BIDAN PRAKTIK SWASTA DI KOTA BANJARBARU - Nia Kania; Lenie Marlinae; Tien Zubaidah (Lambung Mangkurat, 2015)
Abstract To reduce high maternal mortality rate that, one of the efforts that is increase quality service of midwife through standardization midwife private practice. Standard of services obstetric patients have set about service delivery, which aims to ensure for a safe delivery for mother and baby. That is no regulation yet about governs supervision in the organization's health-care private sector, particularly on environmental health, can cause care for sanitation labor has not been throughput by midwife practice private, this is of course will have an effect on the quality service that is given. This research aims to know floor hygiene level, physical quality buildings ,and the labor sanitation facilities, and other environmental health efforts. Types of research that used a survey by the Cross Sectional. Research object is 5 labor’s was the midwife practice private. Data analysis will be done univariat. As many as 60% floor for did not meet the requirements hygiene. Result found that most of the labor have not meet the requirements floor hygiene. The temperature and humidity conditions in all the labors did not meet standardst. Most of the labor that did not meet the requirements lighting, the buildings that were not good, and the effort to revitalize water is not being done with good hygiene, shows that did not meet the requirements floor. Keywords: high clean floors, environmental health, labor, midwife